Acquisitions in the new information universe : core competencies and ethical practices - Holden, Jesse (New York : Neal-Schuman Publishers, 2010)
The work provides an overview of core competencies and the corresponding strategies for dealing with common issues on daily acquisition processes and goals.
The new information universe -- Spheres of access -- Routes to access -- Service and feedback -- Acquisitions in a new paradigm.
Includes bibliographical references and index.
uaj 08/05/13
Loans
Keywords: Acquisitions (Libraries); Acquisition of electronic information resources; Libraries and electronic publishing; Acquisitions (Libraries) -- Technological innovations; Acquisitions (Libraries) -- Moral and ethical aspects; Acquisitions librarians -- Professional ethics